FONDASI PENDIDIKAN MULTIKULTURAL DALAM UPAYA MENCETAK MANUSIA YANG BERKARAKTER - Ansari (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2019)
Indonesia is not only an abundant country with natural resources, but also an abundance of cultural wealth. Cultural richness, if managed properly, can be a source of blessing for this nation, but it contains the potential for conflicts that can divide the unity of the nation. Too often this country has been engulfed in horizontal conflicts stemming from cultural differences. This indicates that public awareness in multiculturalism is still low. In other words, the multicultural character of citizens has not yet been formed. This is where the importance of the foundation of multicultural education in an effort to print human character. Character education needs to be done thoroughly through various sectors of life and this effort needs to be done consciously, planned and integrally. To realize this, a new paradigm in education is needed, namely education with an integrated multicultural approach. Efforts to build character values ??begin with building self and community identity that has strong character in facing the changing times and in accordance with the cultural roots of the nation. These efforts need to be done with an approach that is appropriate to the character of the community. Therefore, through planned and comprehensive and sustainable change, values ??in multicultural education through character education can fill the space of humanity, individual creativity in building their nationalism identity and identity.